2012
DOI: 10.1159/000337178
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of Multidrug Resistance in a Chemoresistant Human Breast Cancer Cell Line by β-Elemene

Abstract: Background: Multidrug resistance (MDR) presents a problem in cancer chemotherapy, and developing new agents to overcome MDR is important. This study intends to investigate the reversal effect of β-elemene on MDR in human breast carcinoma MCF-7 and doxorubicin-resistant MCF-7 cells. Methods: MTT cytotoxicity assays, flow cytometry, and Western blot analysis were performed to investigate the antiproliferative effects of the combination of anticancer drugs with β-elemene, to study the reversal of drug resistance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 82 publications
1
30
1
Order By: Relevance
“…b-elemene is a broad-spectrum antitumor agent. Several studies have indicated that this compound enhances the cytotoxic effect of radiation in vitro and in vivo (Li et al, 2011); in addition it has been reported that it is able to induce apoptosis in human nonsmall-cell lung cancer A549 cells (Liu et al, 2012), and that might represent a promising agent for overcoming MDR in cancer therapy (Xu et al, 2012). a-Humulene was found active against the prostate cancer cells LNCaP (Tundis et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…b-elemene is a broad-spectrum antitumor agent. Several studies have indicated that this compound enhances the cytotoxic effect of radiation in vitro and in vivo (Li et al, 2011); in addition it has been reported that it is able to induce apoptosis in human nonsmall-cell lung cancer A549 cells (Liu et al, 2012), and that might represent a promising agent for overcoming MDR in cancer therapy (Xu et al, 2012). a-Humulene was found active against the prostate cancer cells LNCaP (Tundis et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The extract of elemene is a mixture of β, δ and γ-elemene, with β-elemene as the main component, accounting for 60-72% of the three isoforms. Previous studies have provided abundant evidence to reveal that β-elemene might be an effective MDR reversing agent in cancer chemotherapy and mainly via inhibition of the transport activity of Pgp [3,4]. However the underline mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, BTF has been shown to inhibit DNA damage repair (25,27). This may partly contribute to the fact that β-elemene enhances tumor chemosensitivity or overcomes drug resistance (17,18). The other molecule, Bcl-rambo, is also a pro-apoptotic member of the Bcl-2 family (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, β-elemene was shown to have diverse anticancer potential, such as inhibiting proliferation and inducing apoptosis of cancer cells, and interacting with multiple oncogenic or tumor suppressing signaling pathways in a broad spectrum of cancers (14)(15)(16). Other studies found that β-elemene could enhance tumor chemosensitivity or overcome drug resistance (17,18). In addition, β-elemene has been approved by the China Food and Drug Administration as a therapeutic drug in clinical practice where its efficacy has been exhibited when combined with first-line chemotherapy for malignant tumors (19,20).…”
Section: Introductionmentioning
confidence: 99%